An analysis of intersection traffic signal warrants - Cvitanić, Dražen; Breški, Deana (Promet - Traffic&Transportation, 2005)
This paper presents an analysis of the existing traffic signalwarrants and the cmresponding threshold values. The analysisof unsignalized intersections was conducted according to theanalytical procedures of Highway capacity manual. Traffic signaloptimization was conducted using Synchro software. Theresults showed that the cun-ent wan·ants are not sufficiently reliablein some situations and can be misleading in the process ofselecting the intersection control type. There are three majorreasons for insufficient reliability of the existing wan·ants. First,they are p1imarily based on total major and subject minor streetvolumes, so they do not take into account all the possible combinationsof volume distribution and composition of the turningmaneuvers. Second, they do not make difference betweenthree-leg T intersections and four-leg intersections, and finallythey are based only on an overall system operation without regm·ding the functionality of a specific approach.